The power of the dog : a novel - Savage, Thomas (Back Bay Books, 2021)
"Set in the wide-open spaces of the American West, The power of the dog is a stunning story of domestic tyranny, brutal masculinity, and thrilling defiance from one of the most powerful and distinctive voices in American literature. The novel tells the story of two brothers--one magnetic but cruel, the other gentle and quiet--and of the woman and boy, a mother and son, whose arrival on the brothers' ranch shatters an already tenuous peace. From the novel's startling first paragraph to its very last word, Thomas Savage's voice--and the intense passion of his characters--holds readers in thrall."--Back cover